LITERASI KEUANGAN, GAYA HIDUP DAN PENDAPATAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN PELAKU UMKM - Habib Prawiga; Rita Dwi Putri; Witra Maison (Jurnal Bina Bangsa Ekonomika, 2024)
This study was conducted with the aim of determining the influence of financial literacy, lifestyle and income on financial management behavior in MSME Actors in Tanjung Harapan District, Solok City. This research is a quantitative research with an associative approach. Primary data obtained from respondents with data collection techniques in the form of questionnaires. The population in this study is MSME Actors in Tanjung Harapan District, Solok City, totaling 3089 people and using the slovin technique as a sample, so the population of respondents in this study is 97 MSME Actors. The analysis methods used are validity and reliability tests, normality tests, multicollinearity tests and heteroscedasticity tests, t tests, F tests and coefficients of determination. Hasl hypothesis test partially shows that financial literacy and income have no effect on financial management behavior, while lifestyle has a significant effect on financial management behavior. The results of the hypothesis test simultaneously show that financial literacy, lifestyle and income simultaneously have a significant effect on financial management behavior